Code Switching in Thai Society: Four Decades of Research (International Journal of Language, Literacy and Translation, 2025)
In this paper, the historical developments of different research paradigms and approaches adopted in the studies of Thai English Code Switching (TECS) are critically reviewed. It also critically reflects on future developments of the field deriving from the three positions of TECS in Thai contexts defined as the Emergence, Exploration and Extension periods, along with their major contributions which have been investigated for nearly four decades. Presently, Thai society has inevitably been involved in bilingual and multilingual activities and communities because of the globalisation, internationalisation, and mobilisation, particularly, in the educational systems. Thus,translanguaging such as TECS performed by bilinguals, multilinguals or even monolinguals, has always appeared in different modes of communication. Therefore, there is now a need to underpin the studies of TECS by investigating the Thai variety of English (TE) through TECS features by means of applying the World Englishes Approach propagated by Kachru (1983). This is because the seven paradigms classified in this approach are found to lead to a practical and comprehensible explanation of the TE which exists in Thailand for a long period of time. However, it is still claimed to be in the period of development. Therefore, Kachru’s seven paradigms of World Englishes towards the present or future research of TECS are highlighted in this paper.